Centre-State Relations - Sahni, Sati (New Delhi : Vikas, 1984)
Proceedings of a meeting of leaders of Indian political parties in opposition to the policies of the central government, Srinagar, October 1983
Keywords: Federal government -- India -- Congresses; State governments -- India -- Congresses